Debtor protection in fiduciary guarantee execution during force majeure: a justice analysis of indonesian banking practice - Dermina Dalimunthe; Nasruddin Khalil Harahap (Indonesian Institute For Counseling, Education and Therapy, 2026)
Research This aim for analyze suitability practice execution with principle justice contractual and protection modern law. The methods used is approach juridical normative and juridical empirical, with data sources in the form of regulation legislation, decisions Court Constitution Number 18/PUU-XVII/2019, report performance of OJK and Bank BRI, as well as interview limited with MSME debtors and practitioners law local. This empirical single-case study utilizes a purposive sampling strategy to select a sample size of 15 key informants comprising PT Bank BRI credit risk managers (n=5), legal counsels (n=4), and affected debtors (n=6) to ensure a comprehensive, multi-stakeholder perspective on fiduciary execution disputes. To guarantee research reliability, data collection relied on a semi-structured interview protocol that was rigorously pre-tested and piloted with two legal experts prior to administration. The final sample size was methodologically justified by the attainment of data saturation, which was operationally defined and achieved when three consecutive interviews yielded no novel themes or legal insights. The empirical findings were subsequently evaluated alongside normative statutory materials using qualitative thematic analysis to critically assess the alignment of banking practices with the justice-based principles of modern contract law. In addition that, use contract standard put debtor in position that is not equal and eliminate room negotiation when happen condition force. The principle of renegotiation and hardship in UNIDROIT Principles, as well as draft remedial fairness in Draft Common Frame of Reference (DCFR), offers solution normative going to system law contract more national equitable and adaptive. This article recommend strengthening regulations related execution guarantee fiduciary and improvement role supervision from authority finance in protect interest debtor.